2009
DOI: 10.1111/j.1365-246x.2008.03992.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging and illumination with internal multiples

Abstract: S U M M A R YIf singly scattered seismic waves illuminate the entirety of a subsurface structure of interest, standard methods can be applied to image it. It is generally the case, however, that with a combination of restricted acquisition geometry and imperfect velocity models, it is not possible to illuminate all structures with only singly scattered waves. We present an approach to use multiply scattered waves to illuminate structures not sensed by singly scattered waves. It can be viewed as a refinement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 49 publications
0
58
0
1
Order By: Relevance
“…By propagating wavefields backward in a detailed subsurface model, rather than in a smooth macro model, and crosscorrelating them with their associated source fields in the detailed model, we can image the primary reflections and internal multiples to improve seismic resolution (Youn and Zhou, 2001;Malcolm et al, 2009;Vasconcelos et al, 2010). Because internal multiples are used in this image, this strategy has also been referred to as nonlinear imaging (Fleury and Vasconcelos, 2012;Ravasi et al, 2014).…”
Section: Target-enclosed Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…By propagating wavefields backward in a detailed subsurface model, rather than in a smooth macro model, and crosscorrelating them with their associated source fields in the detailed model, we can image the primary reflections and internal multiples to improve seismic resolution (Youn and Zhou, 2001;Malcolm et al, 2009;Vasconcelos et al, 2010). Because internal multiples are used in this image, this strategy has also been referred to as nonlinear imaging (Fleury and Vasconcelos, 2012;Ravasi et al, 2014).…”
Section: Target-enclosed Imagingmentioning
confidence: 99%
“…The required wavefields may also be computed by evaluating an inverse scattering series (Weglein et al, 2003) or a Bremmer series (Malcolm et al, 2009;Davydenko and Verschuur, 2016). Alternatively, we can estimate the required Green's functions directly from the reflection data that are acquired at the earth's surface by solving a multidimensional Marchenko equation (Broggini et al, 2012;Slob et al, 2014;Wapenaar et al, 2014;da Costa Filho et al, 2015;Singh et al, 2015).…”
Section: Motivationmentioning
confidence: 99%
“…In the RTM case, including multiply-scattered waves in the imaging procedure requires the specific inclusion of a reflector in the velocity model; data requirements for this approach to avoid artifacts is discussed specifically in Mittet (2002Mittet ( , 2006. By contrast, in the one-way framework proposed in Malcolm et al (2009), an estimate of the image of the subsurface is used to include a single reflection in the back-propagation, when the imaging is done within the context of a scattering series such as those discussed in de Hoop (1996); Malcolm et al (2005) or Weglein et al (2003). This latter formulation has the advantage of being able to image with multiply scattered waves without explicitly defining a single reflector, but the formulation has so far been restricted to one-way imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested methodologies for including multiply scattered waves in the imaging procedure to mitigate this problem, for example Jin et al (2006); Malcolm et al (2009) in a one-way framework, and Farmer et al (2006); Jones et al (2007) in reverse-time migration (RTM). In the RTM case, including multiply-scattered waves in the imaging procedure requires the specific inclusion of a reflector in the velocity model; data requirements for this approach to avoid artifacts is discussed specifically in Mittet (2002Mittet ( , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In this dissertation, I propose to implement LSM with reverse time migration (RTM) (Baysal et al, 1983;Whitmore, 1983;McMechan, 1983), where the Green's functions are calculated by finite-difference solution to the full wave equation instead of asymtotic Green's function in Kirchhoff migration (Bleistein, 1987), or one-way solution in one-way wave equation migration (Claerbout, 1985). The advantages include: (1) there is no high-frequency approximation; (2) it has no dip limitations; (3) once the known boundaries, e.g., a salt boundary, are embedded in the migration velocity model, RTM can correctly migrate multiples such as prism waves (Jones et al, 2007;Lu et al, 2008;Malcolm et al, 2009); and (4) phase shifts associated with caustics are taken into account when solving the two-way wave equation.…”
Section: Introductionmentioning
confidence: 99%